2006
DOI: 10.1177/1534734606289507
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Activity and Toxicity of 2 New Hydrogels: A Pilot Study

Abstract: Wound bed preparation remains a very important issue in wound healing. To promote the production of granulation tissue, it is necessary to remove necrotic tissue and to control infection. Necrotic tissue may be removed using a hydrogel preparation. Flaminal and Flaminal Hydro (Flen Pharma, Belgium) are 2 new hydroactive colloid gel dressings with state antibacterial properties. These properties are attributed to an enzymatic complex in their formulation. In the study described in this report, the antibacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…The gold standard for targeted local delivery of antimicrobial agents is antibiotic-impregnated bone cement (polymethylmethacrylate-PMMA); other antibiotic-impregnated biodegradable carriers such as sol-gel coatings [9,10] and hydrogels [11,12] are under development. The use of antibiotic loaded PMMA allows delivery of high concentrations of antibiotics to the affected area without causing systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard for targeted local delivery of antimicrobial agents is antibiotic-impregnated bone cement (polymethylmethacrylate-PMMA); other antibiotic-impregnated biodegradable carriers such as sol-gel coatings [9,10] and hydrogels [11,12] are under development. The use of antibiotic loaded PMMA allows delivery of high concentrations of antibiotics to the affected area without causing systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Neben den oben genannten In-vitro-Studien, die eine antibakterielle, nichtzytotoxische Wirkung der Enzym-Alginogele belegen [7,33] Der molekulare Wirkmechanismus der Enzym-Alginogele auf den Prozess der Wundheilung ist, wie bereits erläu-tert, nicht vollständig geklärt. Es konnte jedoch in einer vergleichenden klinischen Studie anhand einer Stichprobe gezeigt werden, dass mit Enzym-Alginogelen behandelte Wunden eine deutlich höhere Granulation aufwiesen als Wunden, die mit den gleichen Wundauflagen, jedoch ohne Enzym-Alginogele behandelt wurden [16,25].…”
Section: Klinische Studiendatenunclassified
“…Pre-clinical data by Vandenbulcke et al and de Smet et al showed that Flaminal® Forte is not toxic to keratinocytes and fibroblasts in vitro [ 15 , 27 ]. In effect, Flaminal® Forte may not damage skin cells which will finally result in undelayed wound healing.…”
Section: Introductionmentioning
confidence: 99%